CHANGES IN ENDOGENOUS CYTOKININ CONCENTRATIONS IN CHLORELLA (CHLOROPHYCEAE) IN RELATION TO LIGHT AND THE CELL CYCLE(1) - Stirk, Wendy A (Journal of phycology, 2011)
© 2011 Phycological Society of America.